Cannabinoids in the descending pain modulatory circuit: Role in inflammation - Bouchet, Courtney A. (Pharmacol Ther, 2020)
The legalization of cannabis in some states has intensified interest in the potential for cannabis and its constituents to lead to novel therapeutics for pain, and other disorders. Our understanding of the cellular mechanisms underlying cannabinoid actions in the brain have lagged behind opioids. However, the current opioid epidemic has also increased attention on possible uses of cannabinoids for pain, especially chronic pain that requires long-term use. It is now recognized that endogenous cannabinoids are lipid signaling molecules that have complex roles in modulating neuronal function throughout the brain. In this review, we discuss cannabinoid functions in the descending pain modulatory pathway, and highlight areas where further studies are necessary to understand cannabinoid regulation of descending pain modulation.